Growing Up in a Digital World – Digital Media and the Association With the Child’s Language Development at Two Years of Age - Sundqvist, Annette; Koch, Felix-Sebastian; Birberg Thornberg, Ulrika; Barr, Rachel; Heimann, Mikael (Frontiers in Psychology, 2021)
Abstract Digital media (DM), such as cellphones and tablets, are a common part of our daily lives and their usage has changed the communication structure within families. Thus, there is a risk that the use of digital media might result in fewer opportunities for interactions between children and their parents leading to fewer language learning moments for young children. The current study examined the associations between children's language development and early digital media exposure. Participants: Ninety-two parents of 25 months olds (50 boys/42 girls) recorded their home sound environment during a typical day (Language Environment Analysis) and participated in an online questionnaire consisting of questions pertaining to daily digital media use and media mediation strategies, as well as a Swedish online version of the MacArthur Communicative Development Inventory, which includes a vocabulary scale as well as a grammar and pragmatics scale. Results: Through correlations and stepwise regressions three aspects of language were analyzed. The child’s vocabulary was positively associated with interactional turn-taking. The child’s vocabulary and grammar were negatively associated with the likelihood of parent’s device use during everyday child routines and the amount of TV watched by the child. The child’s pragmatic development was also positively associated with the parent’s device use in child routines but also with the parent’s joint media engagement as well as the child’s gender (where girls perform better). Conclusion: Our study confirms that specific aspects of the two-year old’s DM environment are associated with the child's language development. More TV content, whether it is viewed on a big screen or tablet, is negatively associated with language development. The likelihood of parents’ use of DM during everyday child routines is also negatively associated with the child’s language development. Positive linguistic parental strategies such as interactional turn-taking with the child, joint media engagement, and book reading, on the other hand, are positively associated with the child's language development.